VALIDATING A PROJECT LIFE-CYCLE REVIEW FRAMEWORK FOR MINING PROJECTS AT EXXARO - Steenkamp, Jacob Rudolph; Bekker, Michiel Christiaan (The South African Journal of Industrial Engineering, 2018)
Independent formal reviews against validated project frameworks aim to ensure that pre-specified phase deliverables are completed and validated before the next project phase begins. Through various internal initiatives, Exxaro established a project framework to develop and implement capital projects. However, to date, this framework has not been validated. The intent of this research was, through a case study approach, to validate the project framework for Exxaro (a holistic case). Semi-structured interviews were conducted with sixteen key role players across the organisation on four different projects (embedded cases). Results from the embedded cases were compared to identify common themes emerging from the research. Although the research identified areas for improvement for certain aspects of the framework, the common themes correspond with the main aspects of the proposed framework, thus validating the framework.